2005
DOI: 10.1620/tjem.206.319
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Calcium and Other Nutrients Related to Bone Health in Japanese Female College Students: A Study Using the Duplicate Portion Sampling Method

Abstract: The purposes of this study were to determine intakes of nutrients related to bone health, such as calcium (Ca), phosphorus (P), sodium (Na), potassium (K), and protein, in Japanese female college students, using the duplicate portion sampling method, and to identify possible lifestyle factors explaining their calcium intakes. Subjects were 106 Japanese female college students aged 19-23 years. All foods in the duplicate portions, as eaten by the subjects during a three-weekday period, were collected. The miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…However, there is as yet no ideal biological measure of dietary calcium intake for use in epidemiological surveys. The chemical analysis of a homogenate of the duplicate meals consumed by each subject gives an accurate estimate for calcium intake (Ueno et al 2005), but is not feasible in large-scale epidemiological surveys. Several selfadministered diet assessment methods for Japanese people have been validated for various nutrients, including calcium (Sasaki et al 1998;Tsugane et al 2003), but they comprise more than 100 food items and require 40 to 60 min to complete.…”
mentioning
confidence: 99%
“…However, there is as yet no ideal biological measure of dietary calcium intake for use in epidemiological surveys. The chemical analysis of a homogenate of the duplicate meals consumed by each subject gives an accurate estimate for calcium intake (Ueno et al 2005), but is not feasible in large-scale epidemiological surveys. Several selfadministered diet assessment methods for Japanese people have been validated for various nutrients, including calcium (Sasaki et al 1998;Tsugane et al 2003), but they comprise more than 100 food items and require 40 to 60 min to complete.…”
mentioning
confidence: 99%
“…It is assumed that the relationship measured by QUS, that is considered be better accepted for routine health check-ups, indicates the importance of underling food intake in health education to prevent osteoporosis. Several studies have reported on bone mass level and food intake among young women (Sawa et al 2001;Tomita et al 2004;Otsuki et al 2004;Ueno et al 2005;Prynne et al 2006), but the report of a positive relationship between bone mass level and the intake of green and yellow vegetables has been limited. Our result is in line with Otsuki's report demonstrating that intake of green and yellow vegetables showed a correlation with bone mineral density that was measured by DXA at the lumbar spine in young adults (Otsuki et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Peak bone mass yang rendah menyebabkan masalah osteoporosis sehingga tulang mudah patah (Ford, 2007). Kejadian osteoporosis dan patah tulang lebih banyak dialami oleh perempuan terutama bila telah menopause (Ueno, 2005). Salah satu mineral penting yang dibutuhkan untuk proses pembentukan masa tulang adalah J.Gipas, Mei 2019, Volume 3 Nomor 1 ISSN 2599-0152 eISSN 2599-2465 http://jos.unsoed.ac.id/index.php/jgps kalsium (Lesli, 1999).…”
Section: Abstrakunclassified
“…Salah satu mineral penting yang dibutuhkan untuk proses pembentukan masa tulang adalah J.Gipas, Mei 2019, Volume 3 Nomor 1 ISSN 2599-0152 eISSN 2599-2465 http://jos.unsoed.ac.id/index.php/jgps kalsium (Lesli, 1999). Sumber kalsium yang baik dengan avalailabilitas tinggi adalah produk susu seperti keju, mntega, dan yogurt (Lesli, 1999;Drewnowski, 2015 (Rose, 2018;Vatanparast, 2006;Ueno, 2005…”
Section: Abstrakunclassified
See 1 more Smart Citation